2017
DOI: 10.1038/srep46548
|View full text |Cite
|
Sign up to set email alerts
|

Chronic social defeat reduces myelination in the mouse medial prefrontal cortex

Abstract: The medial prefrontal cortex (mPFC) plays a key role in top-down control of the brain’s stress axis, and its structure and function are particularly vulnerable to stress effects, which can lead to depression in humans and depressive-like states in animals. We tested whether chronic social defeat produces structural alterations in the mPFC in mice. We first performed a microarray analysis of mPFC gene expression changes induced by defeat, and biological pathway analysis revealed a dominant pattern of down-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 71 publications
8
100
4
Order By: Relevance
“…Glucocorticoids have been shown to suppress the self-renewal of NSCs derived from the SEZ and the proliferation of OPCs in the white and gray matter of the adult mouse brain (Gould et al 1992;Cameron et al 1993;Alonso 2000;Hitoshi et al 2007). As expected, reduced proliferation of OPCs and subsequent loss of myelin fibers was observed in the frontal cortex of rodent MDD models following chronic stress and this reduction was rescued by treatment with antidepressants or infusion of fibroblast growth factor-2 to the lateral ventricles, which has potential antidepressant properties (Banasr et al 2007;Czeh et al 2007;Elsayed et al 2012;Lehmann et al 2017). Interestingly, the ability of antidepressants to stimulate OPC proliferation appears to be brain region-specific (Kodama et al 2004), suggesting that OPCs localized within regions associated with mood affective disorder are sensitive to chronic psychosocial stress but are also responsive to treatment.…”
Section: Immune System and Psychiatric Disorderssupporting
confidence: 69%
See 1 more Smart Citation
“…Glucocorticoids have been shown to suppress the self-renewal of NSCs derived from the SEZ and the proliferation of OPCs in the white and gray matter of the adult mouse brain (Gould et al 1992;Cameron et al 1993;Alonso 2000;Hitoshi et al 2007). As expected, reduced proliferation of OPCs and subsequent loss of myelin fibers was observed in the frontal cortex of rodent MDD models following chronic stress and this reduction was rescued by treatment with antidepressants or infusion of fibroblast growth factor-2 to the lateral ventricles, which has potential antidepressant properties (Banasr et al 2007;Czeh et al 2007;Elsayed et al 2012;Lehmann et al 2017). Interestingly, the ability of antidepressants to stimulate OPC proliferation appears to be brain region-specific (Kodama et al 2004), suggesting that OPCs localized within regions associated with mood affective disorder are sensitive to chronic psychosocial stress but are also responsive to treatment.…”
Section: Immune System and Psychiatric Disorderssupporting
confidence: 69%
“…; Lehmann et al . ). Interestingly, the ability of antidepressants to stimulate OPC proliferation appears to be brain region‐specific (Kodama et al .…”
Section: Immune System and Psychiatric Disordersmentioning
confidence: 97%
“…In addition to reduced cell densities [85,86] and compromised white matter integrity [87,88] within the cortex and subcortical regions in postmortem tissue collected from the schizophrenia patients, a large set of transcriptomic analyses consistently indicated alterations in myelin-related gene expression networks [8994]. Social isolation and chronic stress, as key environmental risk factors for schizophrenia [95,96], have additionally been shown to irreversibly alter myelination in the PFC of both postnatal and adult mice [34,35,97]. Reductions in NG2-glial density in the PFC and hippocampus have also been reported in rodent models of stress [69,98,99].…”
Section: Association Of Ng2-glia With Neuropsychiatric Disordersmentioning
confidence: 99%
“…It has been increasingly appreciated that myelination and oligodendrocyte development are sensitive to stressful experience, even during adult life (Liu et al, 2012(Liu et al, , 2016Makinodan et al, 2012;Birey et al, 2015;Yang et al, 2016;Lehmann et al, 2017). Neuroimaging studies have demonstrated abnormal myelin structure and reduced oligodendrocyte function that nicely correlated with evidence of decreased oligodendrocyte-related gene expression and reduced oligodendrocyte numbers and density in postmortem human brains from subjects with psychiatric disorders, including major depressive disorder, schizophrenia, and bipolar disorder (Tkachev et al, 2003;Aston et al, 2005;Katsel et al, 2005;Takahashi et al, 2011;Tham et al, 2011;Haroutunian et al, 2014;Birey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%